The Social Disorganization Theory Approach as a Crime Prevention Effort in Sumenep, Indonesia - Tolib Effendi; Rusmilawati Windari; Rayhan Afief Arfarizky (Technium Social Sciences Journal, 2023)
There was an increase in crime rates along with an increase in the number of tourism visitors in Sumenep Regency in the 2017-2019 period. The increase in crime rates mainly occurred in areas that have new high demand tourist objects. The increase in crime is mainly in several forms of crime that can be categorized as social pathology. The increase in crime in tourist sites can be viewed from the point of view of social disorganization theory, namely criminological theory which sees the relationship between crime and geography. This study uses a socio-legal research method that examines the correlation between an increase in the number of tourists and an increase in crime rates in Sumenep and attmpts to prevent crimes committed by the Sumenep Police by using a social disorganization theory approach. There is a concrete correlation between the increase in the number of tourist visitors and the increase in crime according to social disorganization theory, and secondary prevention is carried out by carrying out three prevention policies.